Examining the cognitive demands of analogy instructions compared to explicit instructions. (2nd September 2016) - Tse, Choi Yeung Andy; Wong, Andus; Whitehill, Tara; Ma, Estella; Masters, Rich
Abstract: Purpose : In many learning domains, instructions are presented explicitly despite high cognitive demands associated with their processing. This study examined cognitive demands imposed on working memory by different types of instruction to speak with maximum pitch variation: visual analogy, verbal analogy and explicit verbal instruction. Method : Forty participants were asked to memorise a set of 16 visual and verbal stimuli while reading aloud a Cantonese paragraph with maximum pitch variation. Instructions about how to achieve maximum pitch variation were presented via visual analogy, verbal analogy, explicit rules or no instruction. Pitch variation was assessed off-line, using standard deviation of fundamental frequency. Immediately after reading, participants recalled as many stimuli as possible. Result : Analogy instructions resulted in significantly increased pitch variation compared to explicit instructions or no instructions. Explicit instructions resulted in poorest recall of stimuli. Visual analogy instructions resulted in significantly poorer recall of visual stimuli than verbal stimuli. Conclusion : The findings suggest that non-propositional instructions presented via analogy may be less cognitively demanding than instructions that are presented explicitly. Processing analogy instructions that are presented as a visual representation is likely to load primarily visuospatial components of working memory rather than phonological components. The findings are discussed with reference to speech therapy and human cognition.